Modernizing medical waste management: unleashing the power of Internet of Things (IoT) - Mohamed, Nurul Hamizah; Khan, Samir; Jagtap, Sandeep (MDPI, 2023)
The rapid technological advancements of modern times have brought about the need for an innovative and contemporary approach to medical waste management procedures. This arises from the inadequacy of conventional manual techniques in ensuring the safety of employees and the environment from infections. The increasing amount of waste produced each day can exacerbate the situation if no action is taken to address the current issue. This article presents a systematic review of the use of the Internet of Things (IoT) in medical waste management, utilizing the PRISMA approach. The adoption of the IoT in waste and medical waste monitoring is analyzed for its potential to enhance the overall waste monitoring procedure and contribute to achieving net-zero goals. Empirical evidence from studies conducted in the last five years has revealed the benefits of employing waste bin sensors as a digital surveillance tool for real-time waste status monitoring. While a few researchers have proposed the use of the IoT in medical waste monitoring, the application is currently limited to either monitoring storage facilities, waste transportation, or disposal processes, specifically. These limitations are discussed to understand the barriers that hinder further development. Among the selected analyzed studies are published articles and conference papers that offer solutions for addressing waste management issues and facilitating further development. This paper also aims to identify IoT technologies for monitoring waste and medical waste management. The digitalization of medical waste can ensure that the entire monitoring procedure is conducted directly and in real time. The collected data can be easily shared, and the condition of the waste can be updated periodically.
Keywords: medical waste management; IoT in waste management; contemporary waste monitoring; real-time waste status; net-zero goals; digitalization in waste management; IoT technologies in medical waste management